Un nouveau cursus en conservation-restauration à l’Académie des Beaux-Arts de Kinshasa - Nicole Gesché-Koning (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Thanks to a partnership between the Art Academy in Kinshasa and the Ecole nationale supérieure des arts visuels of la Cambre, 2013 coïncides with the launching in Kinshasa of a new training in conservation-restoration of works of art - Wood and ceramics. An opportunity to question the role and place of the conserver-restorer in Africa.